2002
DOI: 10.1007/s00394-002-0365-3
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherol metabolites 2, 5, 7, 8-tetramethyl-2-(2'-carboxyethyl)-6-hydroxychroman (α-CEHC) and 2, 7, 8-trimethyl-2-(2'-carboxyethyl)-6-hydroxychroman (γ-CEHC) in human serum after a single dose of natural vitamin E

Abstract: alpha-CEHC levels increase after administration of a single dose of natural vitamin E in humans. The appearance of the metabolite in blood parallels that of the parent compound. The gamma-tocopherol analog appears to be metabolized more efficiently than alpha-tocopherol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…When urinary ␣ -CEHC was initially suggested as a biomarker of adequate vitamin E status, the methodology at that time was not suffi ciently sensitive to detect low urinary levels of ␣ -CEHC excreted during times of vitamin E intake only from diet, although plasma ␣ -CEHC increases were reported with supplemental vitamin E intake ( 109,161 ). Refi nements in methodology have shown that low levels of ␣ -CEHC are continuously excreted in urine and do increase with higher ␣ -tocopherol intake (162)(163)(164).…”
Section: Cehc As a Biomarker Of Vitamin E Statusmentioning
confidence: 99%
“…When urinary ␣ -CEHC was initially suggested as a biomarker of adequate vitamin E status, the methodology at that time was not suffi ciently sensitive to detect low urinary levels of ␣ -CEHC excreted during times of vitamin E intake only from diet, although plasma ␣ -CEHC increases were reported with supplemental vitamin E intake ( 109,161 ). Refi nements in methodology have shown that low levels of ␣ -CEHC are continuously excreted in urine and do increase with higher ␣ -tocopherol intake (162)(163)(164).…”
Section: Cehc As a Biomarker Of Vitamin E Statusmentioning
confidence: 99%
“…Although use of g-tocopherol as a supplement has attracted attention, its metabolism in humans is not clearly understood. Radosavac et al (2002) investigated the plasma levels of tocopherols and CEHCs after ingestion of a single dose of vitamin E (306 mg of RRR-a-tocopherol and 1.77 mg of g-tocopherol) and found a significant increase in serum a-tocopherol and a-CEHC levels. Although the g-tocopherol level decreased in their study, an increase in its metabolite g-CEHC was observed (Radosavac et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Radosavac et al (2002) investigated the plasma levels of tocopherols and CEHCs after ingestion of a single dose of vitamin E (306 mg of RRR-a-tocopherol and 1.77 mg of g-tocopherol) and found a significant increase in serum a-tocopherol and a-CEHC levels. Although the g-tocopherol level decreased in their study, an increase in its metabolite g-CEHC was observed (Radosavac et al, 2002). We previously investigated the serum and urine levels of a-and g-CEHC in humans, and reported the elevation of both a-and g-CEHC after high-dose a-tocopherol administration.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate in vivo metabolism of tocopherols, metabolite concentrations have been measured in human urine (5,(7)(8)(9)(10)(11)(12)(13), human plasma (5,(13)(14)(15)(16)(17)(18)(19), and rat bile (20,21). Recently, CEHCs have been reported to have potential health benefits (22)(23)(24)(25) as well as antioxidant functions (26,27).…”
mentioning
confidence: 99%